The Urgency of the Relationship of Ulama and Government in the Development of Religious Diversity in Indonesia - Sazali, Hasan; Sahirman, Sahirman; Tantawi, Iryuha; Abdullah Lawang, Karimuddin (Universitas Nurul Jadid, 2023)
Indonesia is a large country that has residents with various religious and religious backgrounds. As a country with a society of various religions, of course the state will not be able to protect and fulfill all the dynamic needs of its people if there is no support or relationships from elements of the people themselves. So, this is where the government needs relations or partners who can work side by side in realizing peace in religion. In this case, the ulama are one of the government's working partners, so it is necessary to study the urgency of the relationship between the ulama and the government in realizing the development of religious diversity in Indonesia. This research uses qualitative research methods with a schematic sociology approach. The data sources come from various literature, which is then analyzed using qualitative analysis techniques. The results of the research conclude: 1) The relationship between ulama and the Indonesian government in realizing peace is very necessary because society in general is close to ulama so that when ulama unite with the government then the government's call is the ulama's call, what is ordered by the government will be more easily obeyed by the community both in terms of tolerance in religion and in other matters. 2) The development of religious diversity in Indonesia has experienced positive developments, because every religious adherent in Indonesia has provided tolerance for each community, both for the community itself and towards communities of other religions.